Impact of tourism on economic growth and CO2 emissions in the EU: A dynamic panel threshold analysis - Mihajlović, Vladimir; Tubić Ćurčić, Tijana; Lojanica, Nemanja; Mihajlović, Nikolina (Hotel and Tourism Management, 2025)
Purpose – The development of tourism provides significant support for economic growth, and also generates environmental effects that are generally not positive. Accordingly, this paper aims to explore the dynamic effects of tourism development in 27 European Union countries on economic growth and carbon dioxide (CO2) emissions. The objective is to empirically examine the correctness of the tourism-led growth hypothesis (TLGH) and the Environmental Kuznets Curve (EKC). Methodology – The study applies a dynamic panel threshold regression to investigate whether the effects of tourism on economic growth and CO2 emissions change after reaching a certain level of development (threshold). Findings – The research results support the validity of both the TLGH and EKC hypotheses. An increase in tourism development (measured by international tourists’ receipts) stimulates economic growth. Additionally, tourism contributes to a lower marginal increase in CO2 emissions if international tourists’ receipts per capita exceed the threshold of 1,768 or if a country’s GDP per capita surpasses 17,570. Implications – This paper contributes to the theoretical literature of the nexus between tourism, economic growth, and environmental effects by applying an advanced econometric methodology. Empirical research findings show that after reaching a specific development threshold, tourism fosters economic growth while reducing negative environmental impacts.